Interventional MRI-guided catheter placement and real time drug delivery to the central nervous system. (2nd June 2016) - Han, Seunggu J.; Bankiewicz, Krystof; Butowski, Nicholas A.; Larson, Paul S.; Aghi, Manish K.
ABSTRACT: Local delivery of therapeutic agents into the brain has many advantages; however, the inability to predict, visualize and confirm the infusion into the intended target has been a major hurdle in its clinical development. Here, we describe the current workflow and application of the interventional MRI (iMRI) system for catheter placement and real time visualization of infusion. We have applied real time convection-enhanced delivery (CED) of therapeutic agents with iMRI across a number of different clinical trials settings in neuro-oncology and movement disorders. Ongoing developments and accumulating experience with the technique and technology of drug formulations, CED platforms, and iMRI systems will continue to make local therapeutic delivery into the brain more accurate, efficient, effective and safer.